After Cancún climate governance or climate conflicts - Brunnengräber, Achim 1963- (VS research. Energiepolitik und Klimaschu, 2011)
The world is facing several serious challenges at the close of the fossil and nuclear energy regime: the limited resources of cheap conventional oil can only be surmounted by tapping unconventional oil reserves, e.g. deep sea oil. The explosion of the oil platform Deepwater Horizon in 2010 and the subsequent oil spill caused enormous damage, which even a year later cannot be fully estimated. Another even more important threat emanating from the fossil and nuclear energy regime has been brought to our attention by the Fukushima disaster. Last but not least, the problem of climate change caused